Fabrication of Ag3PO4/g-C3N4 heterojunction photocatalyst via in-situ growth and its photocatalytic performance - Shenghui Wen; Yanchun Huang (PLoS ONE, 2025)
Current methods for fabricating heterojunction photocatalysts often involve complex processes and weak interfacial bonding. To address the limitations of complex processes and weak interfacial bonding in existing heterojunction photocatalyst fabrication, this study proposes an in-situ growth method to fabricate an Ag 3 PO 4 /g-C 3 N 4 heterojunction photocatalyst, achieving atomic-level tight interfacial bonding between the two components via in-situ ion exchange. The well-aligned band structures created an internal electric field, which facilitated the migration from the conduction band of graphitic carbon nitride to the valence band of silver phosphate, thereby promoting effective charge separation. Experimental results show that for methylene blue (MB, 5 mg/L) as the target pollutant, the Ag 3 PO 4 /g-C 3 N 4 heterojunction achieves 100% degradation within 15 minutes without any scavenger. In contrast, the Ti 3 C 2 /g-C 3 N 4 composite only reaches 98% degradation for the same MB solution, with a reaction time of 50 minutes (35 minutes longer than Ag 3 PO 4 /g-C 3 N 4 ). For rhodamine B (RhB, 5 mg/L), Ag 3 PO 4 /g-C 3 N 4 reaches degradation equilibrium after 62 minutes with a degradation rate over 96%, while Ti 3 C 2 /g-C 3 N 4 requires 133 minutes to reach 63% degradation for RhB. Under 400 nanometer excitation, graphitic carbon nitride showed intense fluorescence, suggesting that a significant portion of the photogenerated electrons underwent rapid recombination. When the temperature ranges from 15°C to 700°C, titanium carbide/graphitic carbon nitride shows a higher weight loss rate than silver phosphate/graphitic carbon nitride, which maintains a weight loss rate below 1%. Silver phosphate reaches degradation equilibrium after 62 minutes of visible-light irradiation, with a degradation rate exceeding 96%. These results indicate that the heterojunction photocatalyst fabricated by in-situ growth presents excellent photocatalytic activity and stability. It provides an approach for designing efficient and stable Z-scheme heterojunction photocatalysts.